PENEGAKAN HUKUM TERHADAP KENAKALAN ANAK - Widiastuti, Tri Wahyu (Wacana Hukum, 2012)
Abstract:Law enforcement to juvenile delinquency, need looking children with all distinctivenesscharacteristic although child was maturation but situation or environment caninfluence his behaviour. So we must different appreciation and sanction treatment tochild and mature. The goal of law enforcement are defence (protection) to childrenwith concern to the best children, in order to the best future for children.Key word: Law enforcement, juvenile delinquency.